The Development of Physical Fitness Training Models for Prospective TNI and POLRI Students - Muh. Yasa; Widiastuti Widiastuti; Yasep Setiakarnawijaya (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The purpose of this study is to provide an overview and determine the feasibility of the physical fitness training model. This research uses the ADDIE model R&D research method which is planned for 2 months, from April 10 to June 10 2023. The design of this physical fitness training model consists of several training components, namely strength, endurance and speed. The sample in this study was a test of the effectiveness of the Independent High School Bimbel as many as 34 prospective students. The pre-test average score was 62.38 and the post-test average score after being given the physical fitness training model was 76.71, which means that there was an increase in the results from the pretest to the post-test. In the mean difference test with SPSS, mean = -14.324 indicates the difference between the pre-test and post-test, t-count results = -31.537, df = 33 and p-value = 0.000 <0.05, which means there is a difference significant difference between before and after being given the treatment of physical fitness training models. So it can be concluded that the physical fitness training model for prospective TNI and POLRI students is effective for use in fitness training.